2014
DOI: 10.3724/sp.j.1042.2014.01837
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Judgment and Decision Making Research Through the Lens of Fuzzy Trace Theory

Abstract: We present the basic tenets of fuzzy trace theory, a comprehensive theory of memory, judgment, and decision making that is grounded in research on how information is stored as knowledge, mentally represented, retrieved from storage, and processed. In doing so, we highlight how it is distinguished from traditional models of decision making in that gist reasoning plays a central role. The theory also distinguishes advanced intuition from primitive impulsivity. It predicts that different sorts of errors occur wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 91 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…The knowledge questions and marking scheme were informed by Fuzzy Trace Theory, a dual-process theory which proposes two ways in which people process and store information in their memory: (i) processing and remembering the bottom-line meaning (‘gist’), and (ii) processing and recalling information precise details (‘verbatim’) [48]. When making decisions, studies have shown that gist information processing tends to be superior to verbatim processing in improving the quality of the decision, possibly because it relies less on remembering the exact details [49] As such, our knowledge measure was designed to assess whether women understood the ‘gist’ of the information, including their (i) conceptual knowledge of screening for Down syndrome (e.g. screening tells you the chance of having a baby with Down syndrome) and, (ii) numeric knowledge (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The knowledge questions and marking scheme were informed by Fuzzy Trace Theory, a dual-process theory which proposes two ways in which people process and store information in their memory: (i) processing and remembering the bottom-line meaning (‘gist’), and (ii) processing and recalling information precise details (‘verbatim’) [48]. When making decisions, studies have shown that gist information processing tends to be superior to verbatim processing in improving the quality of the decision, possibly because it relies less on remembering the exact details [49] As such, our knowledge measure was designed to assess whether women understood the ‘gist’ of the information, including their (i) conceptual knowledge of screening for Down syndrome (e.g. screening tells you the chance of having a baby with Down syndrome) and, (ii) numeric knowledge (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Decision models that approximate this line of thinking include the fuzzy-trace theory [69], heuristics, like embodied heuristics [70], and intertemporal trade-off model [45]. Fuzzy-trace theory emphasizes categorical differences and predicts that categorical differences between options are encoded as gist representations (e.g., "some money" versus "some money or no money", "all-or-none distinctions", and "low-versus high-danger"), while people will make decisions on the basis of the essential meaning rather than on verbatim expected values [71]. Embodied heuristics, as an early version of ecological psychology, was coined by Gigerenzer [70], that is, innate or learned rules of thumb to facilitate superior decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for Fuzzy-Trace Theory has been reviewed elsewhere (e.g., Reyna, 2012 , Setton, Wilhelms, Weldon, Chick, & Reyna, 2014 ), including the efficacy of health interventions based on the theory (see Blalock & Reyna, 2016 ). However, support for many of the major tenants of Fuzzy-Trace Theory has been “hiding in plain sight” in the classic journal literature.…”
Section: Fuzzy-trace Theory: the View From 35000 Feetmentioning
confidence: 99%